Aquatic Plant–Associated Microbiomes as Biological Clocks for Postmortem Submersion Interval Estimation in Tropical Freshwater: A Proposed Framework - RAJ, RIYA; Caeiro, Don; Katare, Nandini; Raiborde, Mayank David; Thomas, Swetha (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Estimating the postmortem submersion interval (PMSI) is a persistent challenge in the forensic examination of bodies recovered from water. Established approaches like diatom analysis, aquatic entomology, and gross decomposition staging to lose reliability once remains are skeletonized or when seasonal and environmental conditions limit insect and algal evidence. The microbial “necrobiome” provides a complementary line of evidence: during decomposition, microbial communities undergo a time-ordered, reproducible sequence of changes. Methods: We hypothesize that a decomposing body submerged in freshwater alters the microbial communities associated with the biofilms of nearby aquatic macrophytes, notably water hyacinth (Eichhornia crassipes), in a time-dependent manner usable for PMSI estimation. We outline a controlled mesocosm framework that compares three macrophytes, utilising destructive sampling across a 28-day interval, 16S rRNA amplicon sequencing, and supervised machine-learning models. These models are validated by a leave-one-tank-out strategy and an independent run. Results: No data have yet been collected; this communication presents the hypothesis, rationale, and study design. If supported, plant-associated microbiomes could provide an independent PMSI estimator for tropical freshwater settings, a context currently absent from the necrobiome literature. Conclusion: This study presents a hypothesis-driven framework for PMSI estimation based on microbial succession associated with aquatic macrophytes. Experimental validation may establish this approach as a complementary forensic tool for aquatic death investigations in tropical freshwater ecosystems.